PENYIRAMAN TANAMAN BAYAM SECARA OTOMATIS BERDASARKAN KELEMBAPAN DAN WAKTU MENGGUNAKAN ARDUINO UNO - Muhammad Bimo Ferlyando; Putra Dena Pangestu, Ghani Irfan Susanto, Paduloh (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2026)
This research develops an Arduino Uno-based automatic watering system for spinach plants, considering soil moisture and watering time. A soil moisture sensor detects soil conditions in real-time, while an RTC module sets the watering time automatically. The system is designed to turn on when the soil moisture falls below a certain threshold, ensuring the plants' water needs are met efficiently. The results showed improved water use efficiency, quality of plant growth, and reduced dependence on human labor. The system is expected to be an innovative solution to support sustainable agriculture through technological automation.